A generalizable and turnable engineered ecosystem provides a clear route to prosperity and well-being to harness the world’s aquatic “blue” food systems to help end hunger: A perspective - Li, Shengwen Calvin; He, Jian-guo (Frontiers in Food Science and Technology, 2022)
Seafood security is essential in modern society. In 2013, Bush and colleagues stated, ‘Aquaculture, farming aquatic organisms, provides close to 50% of the world’s supply of seafood, with a value of United States 125 billion. It makes up 13% of the world’s animal-source protein (excluding eggs and dairy) and employs an estimated 24 million people’. With the increase in the human population and reducing fishing resources, humans increasingly rely on aquacultural products as the primary protein sources for many countries. Aquacultural productivity has been improving in recent years, and in certain countries, the aquaculture output is more than the fishing output. For example, Chinese aquaculture production is more than fishing output, which provides one-third of animal protein. Thus, intensive aquaculture has become the main supply with global aquatic products (FAO). In recent years, it is estimated that each person consumption of aquaculture products is 130 kg in some countries (Iceland). Here, we illustrate the road blocker in farmed shrimp production and provide our resolution. The global pandemic of white spot syndrome (WSS), caused by the white spot syndrome virus (WSSV), bears a devastating economic loss in farmed shrimp production, thereby jeopardizing seafood security. Currently, there is no effective control for WSS. Conventional single-species intensive farming removes the spatiotemporal interaction between different species. We hypothesize that establishing the spatiotemporal interface of a predator–prey may control WSS outbreak. We search for the pathways for the mechanisms by which predator–prey species interact and compete across spatial scales to characterize WSSV dispersal at regional scales for the local spatiotemporal structure of viral transmission. Thus, we create a generalizable and turnable engineered ecosystem that provides a clear route to prosperity and well-being to harness the world’s aquatic “blue” food systems to help end hunger.